Dealing with scarcity of resources in nursing: the scope and limits of individual responsibility - Primc, Nadia (European Journal for Nursing History and Ethics, 2020)
Empirical studies show that nursing staff are often unable to perform all the nursing tasks they consider necessary. The phenomenon of incompletely performed nursing tasks is a consequence of the scarcity of resources in patient care and represents a form of rationing of nursing care. Although nursing staff cannot be held responsible for the lack of resources, an approach that has considered ethical aspects is necessary for decisions regarding prioritisation and rationing, as well as for considerations regarding efficiency in nursing care for patients. The phenomenon of incompletely performed nursing care should be addressed not only in the context of nursing science and health economics, but also in the context of ethical interpretation. Within the latter context, it is also possible to define in broad terms the scope and limits of individual responsibility of nursing staff under conditions of scarcity.